Certain aspects of informatization of medicines price regulation in Ukraine - Revyatskyy, Ivan (Annals of Mechnikov’s Institute, 2023)
Introduction. A significant part of scientific publications on ensuring the availability of medicines in Ukrainian scientific and specialized publications is devoted, in particular, to the following issues: selection and optimization of methods for calculating prices for medicines and reference pricing, monitoring of prices for medicines, assessment of the availability of medicines, assessment of health technologies (medical technology assessment). The publications also address the issues of pricing for personalized medicines (extemporaneous manufacturing) and accounting for the release of medicines of different groups. However, the aspects of informatization of medicines price regulation from the point of view of pharmaceutical informatics have not been specifically considered. Therefore, the purpose of the study was to analyze the presented structures of information on nomenclature items of medicinal products in the regulatory legal acts on the regulation of prices for medicinal products in Ukraine. Based on the data obtained: to substantiate the feasibility of using a single identifier of the nomenclature position of a medicinal product in regulatory legal acts, to determine and systematize the format, scope and level of its application; to identify possible ways to reduce the number of regulatory legal acts regulating the prices of medicinal products in Ukraine. Material & methods. The objects of the study were information sources on the state regulation of pricing for medicines: regulatory acts, analytical documents, official websites of government agencies and specialized publications, scientific works of domestic scientists. The following methods were used in the study: descriptive statistics, systematization, grouping and generalization of the results. Results & discussion. The article analyzes the state of information on nomenclature items of medicinal products in the regulatory legal acts of the Ministry of Health of Ukraine on pricing: international nonproprietary names / common names of active pharmaceutical ingredients, names of manufacturers of medicinal products and codes of anatomical, therapeutic and chemical classification. The results of the work are presented as statistical data and examples of non-standardized names of the above objects. Based on the data obtained, the problems caused by the state of submission of non-standardized information are described and ways to solve them are proposed. Conclusion. The basic method of information structure for recording information about medicinal products in the relevant registers and regulatory acts with regard to unique identifiers of nomenclature items is proposed. The author substantiates the need to create and use unified registers to ensure the possibility of automated generation of information on nomenclature items of medicinal products for regulatory legal acts. The lack of unified standards for the presentation of information on medicinal products in regulatory acts and medicinal product identifiers makes it impossible to use automated methods of information analysis, especially in the time dynamics. This, in turn, makes it impossible to use the results of the analyzes when making forecasts. The current structure of regulation and information provision may lead to cases where information in some regulations contradicts each other. The constant change in the validity of regulatory legal acts makes it impossible to create an up-to-date permanent reference to the latest information, and creates additional difficulties for practicing pharmacists who must comply with the standards and data specified in these legal acts in their daily work. The author substantiates the expediency of creating a single regulatory legal act on the regulation of prices for medicinal products for each of the regulatory authorities/structures. The author proposes to create a single legally approved URL with only relevant information on pricing aspects and the availability of an online chat and a public web forum where experts will provide quick responses to requests from practitioners. Keywords: information, identification, standardization, regulations, registers, wholesale prices